2006
DOI: 10.1177/1049732305281597
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support and HIV/AIDS Medication Adherence Among African American Women

Abstract: HIV/AIDS incidence is increasing more quickly among women than any other segment of the population. The typical woman with HIV/AIDS is young, in her late 20s, economically challenged, and of childbearing age. Adherence to HIV therapies is critical if patients are to achieve and maintain virologic suppression. The author recruited HIV/AIDS-infected African American women from an outpatient clinic to investigate the women's perceptions of social support and how it affected their medication adherence. She collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 29 publications
5
125
0
4
Order By: Relevance
“…Social support plays role of moderator in different coping strategies. According to Edwards [13] factors which enhance adherence of treatment of HIV/AIDS in women family support and having children, while factors which create hindrance in treatment are lack of emotional support and having partner with HIV/AIDS.…”
Section: Aids (Acquired Immune Deficiency Syndrome Is) Caused By a VImentioning
confidence: 99%
“…Social support plays role of moderator in different coping strategies. According to Edwards [13] factors which enhance adherence of treatment of HIV/AIDS in women family support and having children, while factors which create hindrance in treatment are lack of emotional support and having partner with HIV/AIDS.…”
Section: Aids (Acquired Immune Deficiency Syndrome Is) Caused By a VImentioning
confidence: 99%
“…In addition, while taking medication in the public may signify a person's serostatus status, individuals with high level of stigma may skip their medication to avoid disclosure of serostatus (Edwards, 2006;Ware et al, 2006).…”
Section: Factors Associated With Intentional Nonadherencementioning
confidence: 99%
“…40 As the evidence levels, 8 there was the following distribution: an article level II, 31 an article level IV 11 articles level VI. 1,[9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][32][33][34][35][36][37][38][39][40] It was found that most of the findings were derived from cross-sectional and descriptive studies, occurring direct observation of a planned number of people with HIV/ AIDS in a lifetime opportunity, which prevents comparisons of long-term sample characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The main barriers to adherence to ART are stigma and turbulent romantic relationships. 32 Social support and positive coping increase the adherence to ART. 40 Satisfaction with social support and coping were the best positive predictors of adherence to ART.…”
Section: Social Support and Adherence To Artmentioning
confidence: 99%